Living with Diabetes: The Right Approach - Nancy J. Gal; Linda B. Bobroff (EDIS)
Revised! FCS-8542, a 10-page illustrated fact sheet by Nancy Gal and Linda Bobroff, describes the different kinds of diabetes and the risk factors for each. It explains tests and treatments and describes lifestyle choices that can help those with the disease live longer and healthier lives. This version includes new wording and some changes in clinical knowledge. Published by the UF Department of Family, Youth and Community Sciences, October 2006.